2008
DOI: 10.1021/la801589q
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Block Copolymer Monolayers by Adsorption from Supercritical Fluids: A Versatile Concept for Modification and Functionalization of Polymer Surfaces

Abstract: We describe a generic method for polymer surface modification and functionalization that is applicable for substrates of arbitrary shape. The method involves the deposition of monolayer and submonolayer films of photoactive block copolymers from supercritical fluids. Poly(styrene-b-tert-butyl acrylate), poly(S-b-tBA), block copolymer monolayers form spontaneously on polystyrene substrates by adsorption from scCO2 when hexane is used as a cosolvent. Atomic force microscopy indicates the films are flat and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The solubility of a block copolymer generally falls between that of its two homopolymers. 29 As various authors have reported that the solubility of scCO2 of polymers is only significantly influenced by pressure and temperature and almost independent of the molar mass of PS and PEO, 31,[35][36] it seems unlikely that the cause of enhanced phase separation is related to a swelling effect leading to greater free volume and increased chain mobility.…”
Section: Microphase Separation Of Higher Molecular Weight Bcpmentioning
confidence: 99%
See 2 more Smart Citations
“…The solubility of a block copolymer generally falls between that of its two homopolymers. 29 As various authors have reported that the solubility of scCO2 of polymers is only significantly influenced by pressure and temperature and almost independent of the molar mass of PS and PEO, 31,[35][36] it seems unlikely that the cause of enhanced phase separation is related to a swelling effect leading to greater free volume and increased chain mobility.…”
Section: Microphase Separation Of Higher Molecular Weight Bcpmentioning
confidence: 99%
“…23,29,31 Figure 7 shows the ratio of swelling for PS:PEO as a function of pressure and temperature, highlighting that the ratio decreases with pressure ( Figure 7a) and increases with temperature ( Figure 7b). These data are attributed to the fact that the rate of increase or decrease of swelling of PEO with pressure and temperature respectively is much faster than that of PS.…”
Section: Effect Of Depressurization Ratementioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon was known as that block copolymers self-assemble and order at the surface of a homopolymer substrate [11] . One block of this kind of block copolymers is usually identical to the substrate and serves to anchor the block copolymer into the substrate; the second block generally comprises a lower surface tension polymer containing functional groups and forms a surface layer at the airpolymer interface via preferential surface segregation [9,12,13] . The block of lower surface tension therefore delivers its functional groups to the surface of substrate and produces desirable interfacial properties.…”
Section: Introductionmentioning
confidence: 99%
“…[2,8,13] In the past several practical approaches have been explored for the modification of polymer surfaces, including chemical reactions, [11,[14][15][16][17] blending, [18] plasma treatments, [19] corona discharge treatments, [20] grafting reaction [21] and adsorption of block copolymers. [22] Unfortunately, many of these surface modification methods may come with drawbacks such as added costs, a limited range of chemistries, lack of durability and increased potential for bulk polymer degradation. [23] In fact, to improve the properties of poly(vinyl chloride) (PVC), our group has been devoted to investigate the modification of the pristine material, via nucleophilic substitution of chlorine atoms, in bulk [11,24,25] and at the surface using mixtures of solvents and non-solvents for the polymer.…”
Section: Introductionmentioning
confidence: 99%